An Ideological Analysis of the Former President Donald Trump’s Tweets During the COVID‑19 Pandemic - Giulia Magazzù (Testo & Senso, 2022)
The aim of the present study is to explore the former US President Donald Trump’s representation of "us" and "others" in his tweets related to COVID-19 and how he portrayed the representation of "us" and "others." The sample for COVID-19 in this study was made up of tweets issued by former US President Donald Trump between January and May 2020. The ideological framework proposed by Van Dijk (1997) was used to analyze the ideological discourse of former President Donald Trump's tweets during COVID-19 to reveal the underpinning motivations and viewpoints of us-representation and others-representation. According to the results of this study, Donald Trump depicted a favorable us-group and a negative others-group. Furthermore, former President Trump's typical tactics for portraying both groups included argumentation or authority, juxtaposition, recurrence, emphasis, and analogies. It was also discovered that there was inconsistency between the positive attitudes towards the us-group and negative attitudes about the others-group. When the same descriptions were given to both groups, for example, there were adjustments, which may or may not have been consistent with the groups' underlying goals or interests. The research findings may help analyze former President Donald Trump's Twitter discourse, a comparatively new source of political information.